Estrutura de terras e acesso a bens produtivos no Sul do Brasil: Um estudo a partir do censo agropecuário de 2017 - Mengel, Alex Alexandre (2022)
This article aimed to understand whether a greater or lesser availability of land per establishment interfere in their socio-productive insertion, as well as to understand the relationship between the establishment's area size and its demand for goods and services from other sectors. To this end, the article was dedicated to analyzing information provided by the 2017 Agricultural Census, carried out by the IBGE. The socio-spatial focus for the study was the Southern Region of Brazil. It was found that farmers who own a low volume of land are doubly harmed, firstly, because they do not have the land and other natural resources associated with it at their disposal, and secondly, because they have access to goods and services necessary for the development of their activities hampered.